A Duna menti homoki gyepek biomasszája - Rácz, Brigitta; Fűrész, Attila; Péter, Norbert; Stilling, ferenc; Pajor, Ferenc (Gyepgazdálkodási Közlemények, 2021)
Festuca taxa are important grassland species in the pannonian vegetation, and are defining members of it where conditions are too extreme for most plants. Based on grassland management surveys, habitats of narrow-leaved or small Festuca species are an indicator of poor productive capacity, but are important in terms of nature conservation. The significance of these grasslands are likely to be increasing in line with climate change and expanding dry habitats.